Perlindungan Hukum Terhadap Produk Elektronik Yang Tidak Disertai Kartu Garansi - I Gusti Ngurah Agung Wahyu Krisna; I Made Minggu Widyantara; Anak Agung Istri Agung (Fakultas Hukum, Universitas Warmadewa, 2022)
Warranty or is proof that if the disability when the assembly of an object will be guaranteed that the item will be exchanged because of the disability and material defects at the time unknown. In general, the guarantee is following Uupcons and Permendagri No.019 / M-DAG / PER / 05/2009 which regulates Sales Guarantee Assurance / Indonesian Language Warranty Cards. It works to find the legal consequences for economic perpetrators of electronic products without collateral and to seek legal protection for electronic products without collateral. This research is an (Empirical Research of Law), the distribution of investigations is a process that immediately descends directly into the field and is a party with related communities. This research system is an explanation or description so that the sulbactam understands the description. Primary and secondary tools act as a data source. 1. As a result of the law of electronic products without a warranty, the certificate is a punishment that must be taken care of by managing or payment and listed in the uupkonsumen of it as soon as possible to PSL 60. 2. There is also a provision of assistance by regulations regarding electrical goods when not guaranteed.